Efficacy and Safety of an Anti-nerve Growth Factor Antibody (Frunevetmab) for the Treatment of Degenerative Joint Disease-Associated Chronic Pain in Cats: A Multisite Pilot Field Study - Gruen, Margaret E.; Myers, Jamie A. E.; Lascelles, B. Duncan X. (Frontiers in Veterinary Science, 2021)
Background: Pain management for cats with degenerative joint disease (DJD) remains a critical unmet need. Recent work has shown promise for a feline-specific anti-nerve growth factor monoclonal antibody (frunevetmab) to deliver safe and effective pain management. Our objectives were to evaluate efficacy and safety of frunevetmab administered twice using two administration routes (subcutaneous and intravenous) compared to placebo. Methods: This was a randomized placebo-controlled, double-masked study. After a week-long pain and activity baseline, 126 cats were randomized to receive injections of frunevetmab (IV then SC; n=42 or SC then SC; n=43) or placebo (IV then SC; n=4)1on Days 0 and 28. Owners completed questionnaires on Days 14, 28, 42, and 56. Accelerometry data were collected continuously throughout. Results: Owner questionnaire results showed significant improvement in frunevetmab-treated cats (compared to placebo; (p < 0.05)) at Days 42 and 56; no difference was found between routes of administration for frunevetmab. All groups had decreased objectively measured weekly activity from baseline; frunevetmab-treated cats had a mean decrease of 0.9%, whilst placebo-treated cats had a mean decrease of 9.3%. Treatments were generally well-tolerated. The majority of adverse events included dermatitis/alopecia related to activity-monitor collars; these occurred in a higher percentage of frunevetmab, compared to placebo, treated cats. Conclusions and clinical relevance: Treatment with frunevetmab provided improvements in owner ratings of mobility over treatment with placebo; these results were supported by objectively measured accelerometry. Frunevetmab has the potential to address a critical gap in the treatment of chronic pain in cats.